Characterization of cucumber mosaic virus isolated from yam (Dioscorea spp.) in West Africa - Eni, A.; Kumar, P. Lava; Asiedu, Robert; Alabi, O.J.; Naidu, R.; Hughes, J.; Rey, M.E.C. (Academic Journals, 2013)
Millions of people in the West African sub-region depend on yam for food and income. In 2008, cucumber mosaic virus (CMV), one of the most economically important plant viruses was detected in yam fields in Ghana, Benin and Togo, three of the five topmost yam producing countries in the world. Some strains of CMV are reportedly more virulent than others thus the need to characterise the strain isolated from yam. Sap inoculation of the yam strain induced systemic mosaic on Cucumis sativus and systemic chlorosis, necrotic lesions and leaf distortion on Nicotiana glutinosa. Sequence analysis of the 3' end of the coat protein gene and C-terminal noncoding region revealed 98 to 99, 93 to 98 and 78 to 79% nucleotide homology with members of the subgroups IA, IB and II, respectively. This analysis further revealed the absence of the EcoR1 restriction site characteristic of subgroup II strains and the presence of 15 nucleotide deletions dispersed along the C-terminal noncoding region of subgroup IA strains. At the amino acid level, the virus had 99 to 100% homology with subgroup I strains and 89% homology with subgroup II strains. Phylogenetic analysis of the amino acid confirms that the yam strain of CMV belongs to subgroup I while nucleotide sequence phylogeny confirms its placement in subgroup IA.